2020
DOI: 10.1007/s12551-020-00769-3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the putative anticancer alkaloid chelerythrine with nucleic acids: biophysical perspectives

Abstract: Alkaloids represent an important group of molecules that have immense pharmacological potential. Benzophenanthridine alkaloids are one such class of alkaloids known for their myriad pharmacological activities that include potential anticancer activities. Chelerythrine is a premier member of the benzophenanthridine family of the isoquinoline group. This alkaloid is endowed with excellent medicinal properties and exhibits antibacterial, antimicrobial and anti-inflammatory properties. The molecular basis of its t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Combined with the experimental data of this study, from the testing standards specified in the PPRC, the Z. nitidum quality, based on the nitidine chloride content, of Guangdong Province is identified to be superior to that from Guangxi Province. In addition, this study extracted alkaloids such as chelerythrine, magnoflorine, and sanguinarine chloride, which were reported to have anti‐inflammatory (Xu et al, 2020), antibacterial (Xu et al, 2020), antitumor (Basu & Kumar, 2020; Heng & Cheah, 2020), anti‐COVID‐19 (anti–coronavirus disease 2019), and other viral (Ghashghaeinia et al, 2020; Valipour et al, 2021) pharmacological effects; further, these were the main components in Z. nitidum responsible for its medicinal effects. The contents of the four alkaloids detected in samples S1–S3 from Guangdong Province were found to be higher than those found in samples S4–S8 from Guangxi Province.…”
Section: Resultsmentioning
confidence: 99%
“…Combined with the experimental data of this study, from the testing standards specified in the PPRC, the Z. nitidum quality, based on the nitidine chloride content, of Guangdong Province is identified to be superior to that from Guangxi Province. In addition, this study extracted alkaloids such as chelerythrine, magnoflorine, and sanguinarine chloride, which were reported to have anti‐inflammatory (Xu et al, 2020), antibacterial (Xu et al, 2020), antitumor (Basu & Kumar, 2020; Heng & Cheah, 2020), anti‐COVID‐19 (anti–coronavirus disease 2019), and other viral (Ghashghaeinia et al, 2020; Valipour et al, 2021) pharmacological effects; further, these were the main components in Z. nitidum responsible for its medicinal effects. The contents of the four alkaloids detected in samples S1–S3 from Guangdong Province were found to be higher than those found in samples S4–S8 from Guangxi Province.…”
Section: Resultsmentioning
confidence: 99%
“…While the mechanism through which sanguinarine and its analogs inhibit MKP1 is unknown, the benzophenanthridine pharmacophore can be used as a basis for structure-activity relationship (SAR) studies for the development of more potent and selective MKP1 inhibitors ( 57 ). Despite these data, it is highly unlikely that either sanguinarine or chelerythrine exerts MKP-specific effects to be useful tool compounds, given that these compounds exhibit numerous cellular responses on many other targets ( 59 , 60 ).…”
Section: The Mkp Inhibitor Challengementioning
confidence: 99%
“…Chelerythrine chloride (CHE, Scheme ), one of the most representative and commercially available QBAs, is mainly isolated from edible and medicinal plants of greater celandine Chelidonium majus L. and M. cordata. , A variety of reported pharmacological properties of CHE include antitumor, antibacterial, antimicrobial, anti-inflammatory, antiplaque, adrenolytic, and local anesthetic effects. , It has also been found that CHE is a prominent compound for the treatment of COVID-19 in recent years . Due to these unique merits, CHE is commonly applied to health foods and animal feeds as a nutritional and functional additive .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 A variety of reported pharmacological properties of CHE include antitumor, antibacterial, antimicrobial, anti-inflammatory, antiplaque, adrenolytic, and local anesthetic effects. 6,7 It has also been found that CHE is a prominent compound for the treatment of COVID-19 in recent years. 8 Due to these unique merits, CHE is commonly applied to health foods and animal feeds as a nutritional and functional additive.…”
Section: ■ Introductionmentioning
confidence: 99%